2016
DOI: 10.3109/01942638.2015.1126880
|View full text |Cite
|
Sign up to set email alerts
|

Current Rehabilitation Practices for Children with Cerebral Palsy: Focus and Gaps

Abstract: While body functions and structure are well-addressed, other ICF elements, specifically participation, are poorly integrated into practice. The emerging focus on the environment in therapy intervention, by modifying the context rather than changing aspects of the child, is consistent with current approaches and evidence. Knowledge translation implementation initiatives are recommended to bridge identified gaps.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
49
0
10

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(65 citation statements)
references
References 24 publications
6
49
0
10
Order By: Relevance
“…The large age-range of participants, the range of settings that participants worked in, and the wide range of regions of the UK that participants worked in, however, suggests that the sample is representative of the population of physiotherapists who work with adolescents with CP in the UK. The number of respondents is also similar to that in previous studies that assessed current rehabilitation practices for children with CP using a survey (Anaby et al, 2016;Saleh et al, 2008).…”
Section: Discussionsupporting
confidence: 56%
“…The large age-range of participants, the range of settings that participants worked in, and the wide range of regions of the UK that participants worked in, however, suggests that the sample is representative of the population of physiotherapists who work with adolescents with CP in the UK. The number of respondents is also similar to that in previous studies that assessed current rehabilitation practices for children with CP using a survey (Anaby et al, 2016;Saleh et al, 2008).…”
Section: Discussionsupporting
confidence: 56%
“…In summary, these initial findings may encourage clinicians to re‐think the focus of practice, recognizing that body‐functions may be improved through engaging in activities of choice. This is important given the existing knowledge‐to‐practice gaps where attention is mostly directed towards body functions and task‐oriented activities (mobility, dressing) rather than to community participation . Thus, findings can support an initial shift in practice towards interventions that can potentially achieve both outcomes simultaneously: participation and body functions.…”
Section: Discussionmentioning
confidence: 92%
“…This is important given the existing knowledge-to-practice gaps where attention is mostly directed towards body functions and task-oriented activities (mobility, dressing) rather than to community participation. 39 Thus, findings can support an initial shift in practice towards interventions that can potentially achieve both outcomes simultaneously: participation and body functions. Such interventions are likely to be successful, as they are socially engaging and motivating, and thus can increase adherence to treatment and sustainability after their completion.…”
Section: Not Applicable Uumentioning
confidence: 99%
“…Authors of the studies identified for this scoping review were predominantly physiotherapists; a survey of Canadian HCPs working with children with CP found that physiotherapists choose interventions focused on BSF domains. 81 Physiotherapists tend to use therapeutic exercises to promote maximum movement and functional ability, 82 while occupational therapists tend to have a greater focus on modifying the environment or the task to help a client succeed. 83 Occupational therapy is taught at only 14 colleges in India 84 whereas more than 200 physiotherapy colleges exist.…”
Section: Discussionmentioning
confidence: 99%